Proinflammatory doses of diesel exhaust in healthy subjects fail to elicit equivalent or augmented airway inflammation in subjects with asthma. Issue 1 (13th September 2010) - Behndig, Annelie F; Larsson, Nirina; Brown, Joanna L; Stenfors, Nikolai; Helleday, Ragnberth; Duggan, Sean T; Dove, Rosamund E; Wilson, Susan J; Sandstrom, Thomas; Kelly, Frank J; Mudway, Ian S; Blomberg, Anders
Abstract : Background: Exposure to traffic-derived air pollutants, particularly diesel emissions, has been associated with adverse health effects, predominantly in individuals with pre-existing respiratory disease. Here the hypothesis that this heightened sensitivity reflects an augmentation of the transient inflammatory response previously reported in healthy adults exposed to diesel exhaust is examined. Methods: 32 subjects with asthma (mild to moderate severity) and 23 healthy controls were exposed in a double-blinded crossover control fashion to both filtered air and diesel exhaust (100 μg/m 3 PM10 ) for 2 h. Airway inflammation was assessed by bronchoscopy 18 h postexposure. In addition, lung function, fraction of exhaled nitric oxide and bronchial reactivity to metacholine were examined in the subjects with asthma. Results: In healthy control subjects a significant increase in submucosal neutrophils (p=0.004) was observed following the diesel challenge. Significant increases in neutrophil numbers (p=0.01), and in the concentrations of interleukin 6 (p=0.03) and myeloperoxidase (p=0.04), were also seen in bronchial wash after diesel, relative to the control air challenge. No evidence of enhanced airway inflammation was observed in the subjects with asthma following the diesel exposure. Conclusions: Exposure to diesel exhaust at concentrations consistent with roadside levels elicited an acute and active neutrophilic inflammation in the airways of healthy subjects. This response was absent in subjects with asthma, as was evidence supporting a worsening of allergic airway inflammation.